Production of activated carbon from waste coconut shell via microwave irradiation carbonization system for supercapacitor electrode / Mohd Iqbaldin Mohd Nayai - Mohd Nayai, Mohd Iqbaldin (2013)
Activation process for coconut shell was done by using chemical activation method of microwave-induced KOH technique in order to reduce the production time. The activation process was successfully carried out at power level of 100 to 1000W with irradiation time and impregnation ratio of 10 to 30min and 1.0 to 3.0, respectively. The surface area and pore size, surface morphology and specific capacitance of activated carbon produced were analyzed by using an automatic Quantachrome Instrument (AutosorblC) volumetric sorption analyzer, Scanning Electron Microscope (SEM) and Automatic Battery Cycler, respectively. The best product produced at 20min of irradiation time with power level and impregnation ratio of 600W and 1.5 has a maximum surface area and specific capacitance value of 1768.8m2g'' and 156.33Fg"', respectively with the pores size range in mesopores (2.745nm) and 58% product yield. Response Surface Methodology (RSM) was used in order to get an optimum condition for the activation process. Three independent variables were chosen i.e. irradiation time, impregnation ratio and KOH concentration. Using RSM, the best conditions were chosen with irradiation time of 17.77min, impregnation ratio of 1.92 and concentration of KOH of 15%. It was found that the model used to get an optimal condition of coconut shell-based activated carbon (CSAC) seems to be valid with a model desirability of 0.810. Thus, based on the findings it can be concluded that the microwave irradiation system can be used as an alternative heating method to produce activated carbon in order to reduce the activation time.